The Spanish flag over an Anglo-Chinese commercial colony the Philippines in the 19th century - Legarda, Benito Jr. ([Quezon City] School of Economics, University of the Philippines, 2012)
Nineteenth-century Philippines, unlike most colonies, was not economically dependent on its mother country, Spain, which ranked generally only fourth among its trading partners, behind the United Kingdom, the United States, and China. The index-measured concentration of Philippine trade was only moderately high owing to competition among its trading partners. Foreign trading was mainly conducted by the British and Americans. The Chinese were pervasive in domestic trade. Thus arose the jibe that the Philippines was an Anglo-Chinese colony with a Spanish ﬂag. With the growth of foreign trade, wealth circulated into the rural areas, assisting in the rise of a native middle class. But there were costs, among them the destruction of the domestic textile industry. With the coming of the United States, the Philippines once again came under a unitary politico-economic metropole, leading to a high degree of economic complementarity lasting until long after World War II.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 49-50)
Keywords: Commerce -- Philippines -- 19th century; International trade -- 19th century